Pleasantness shapes congruency effects in odor-induced taste enhancement - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

Bioaerosols in the atmospheric environment of oil exploitation sites: spatial and temporal distribution, sources, influencing factors, health risks, and reduction efficiency of masks - Hongjie Yang; Shen He; Zongting Yao; Hao Li; Qihao Feng; Simin Huang; Zhen Chen; Jiasheng Ni; Zhishu Liang (Environmental Pollution, 2026)

Low-dose sodium acetate-mediated energy compensation stabilizes oxygen-limited urea hydrolysis coupled with partial nitritation/anammox for high-strength urea wastewater treatment - Meng Yang; Yonggan Li; Yongxing Chen; Yu Zhang; Yasong Wang; Qingyu Liu; Simin Lu; Xiaojun Wang (Bioresource Technology, 2026)

Seasonal hydrology shapes the spatiotemporal distribution of microplastics, antibiotics, ARGs, and sediment bacterial communities in the water-sediment interface - Yurui Zhang; Wei Wang; Xin Meng; Jingyan Hao; Jingru Yang; Simin Li (Journal of Environmental Chemical Engineering, 2026)

Toxic mechanisms and biomarkers of Staphylococcus aureus aerosol exposure to human respiratory cells at the air-liquid interface - Zhishu Liang; Yanran Wu; Jiasheng Ni; Yunling Yang; Simin Huang; Xiaofeng Jiang; Xinhui Bi (Environmental Pollution, 2026)

Icing distribution characteristics on wind turbine blades and their implications for anti-/de-icing element layout - Simin Li; Lixin Yang; Yiqi Liu; Haojie Zhang; Jiale Yu; Yuchen Zhou (Cold Regions Science and Technology, 2026)

Coupled impact of air-conditioning anthropogenic heat and building cooling energy consumption in high-density old urban neighborhoods - Simin Yang; Yunfei Ding; Chengliang Fan; Wanling Lin; Dongyu Lian; Yundan Liao (Building and Environment, 2026)

HtpsB, a type II histidine triad protein of Streptococcus suis, contributes to bacterial virulence and blood-brain barrier disruption - Jingyan Fan; Jinpeng Zhang; Baiyi Chen; Yixin Han; Hexiang Jiang; Simin Deng; Luqing Cui; Xiaolu Lai; Kalliopi Rantsiou; Luca Simone Cocolin; Rui Zhou; Houhui Song; et al. (Veterinary Microbiology, 2026)

Aggregation-induced emission photosensitizers for photodynamic food packaging: Antibacterial mechanisms, material innovations, and applications - Wenxin Wang; Shutian Sun; Simin Fan; Qingfeng Yang; Dequan Zhang; Chengli Hou (Trends in Food Science & Technology, 2026)

Molecular-weight modulation improves the physicochemical properties and in vitro release behavior of spray-dried Agaricus bisporus polysaccharide microcapsules - Simin Feng; Jiaxin Dai; Tingxuan Zong; Manyu Zhang; Pu Yang; Yuyan Wang; Kseniya Hileuskaya; Yizhen Xie; Ping Shao (Food Bioscience, 2026)

Toward heat mitigation II: Effect of rooftop photovoltaics on summertime near-surface air temperature and building cooling energy demand across local climate zones - Yundan Liao; Dongyu Lian; Simin Yang; Chengliang Fan (Energy and Buildings, 2026)

Corrigendum to “Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties” [Food Res. Int. 214 (2025) 116601] - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2026)

Integrated transcriptomic and metabolomic analysis of intestinal responses of Litopenaeus vannamei under acute freshwater stress - Xuenan Li; Huici Yang; Simin You; Nauman Khan; Xilin Dai (Aquatic Toxicology, 2026)

Unraveling threshold effects and hierarchical mechanisms of spatial mismatch between urban environment and subjective well-being in megacities - Yuheng Tu; Yang Wu; Xiong Zheng; Simin Tao (Landscape and Urban Planning, 2026)

Acetochlor disrupts the maternal effect of food restriction in lizards (Eremias argus): Evidence from intergenerational growth and embryonic development - Yue Zhang; Yufan Nie; Simin Yu; Yuping Liu; Hao Yang; Jiajing Sun; Dier Song; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Journal of Hazardous Materials, 2026)

Green and sustainable dual-pathway strategies for high-efficiency photoconversion of ergosterol to vitamin D₂ from agaricus bisporus - Jiahao Yu; Yan Tang; Yang Lin; Simin Feng; Mofei Shen; Ping Shao (Food Chemistry, 2026)

Pumping Optimization for Groundwater Remediation Under Uncertainty Using an Improved Hiking Optimization Algorithm - Xuemin Xia; Yujie Yang; Simin Jiang; Xianwen Li (Water, Air, & Soil Pollution, 2026)

Complementary Protective Effects of Lactiplantibacillus Plantarum GUANKE and Picolinic Acid Against Influenza A Virus Infection in Mice - Jielan Mi; Kun Yue; Xiao Zhang; Yuewen Yang; Simin Lu; Yujia He; Zhihan Yang; Siqin He; Yuanming Huang; Liqiong Song; Zhihong Ren; Jianguo Xu (Probiotics and Antimicrobial Proteins, 2026)

Micro-electrostimulation facilitates hydrolysis-acidification process for pretreatment of toxic and refractory organic wastewater: Mechanisms, influencing factors, and applications - Simin Li; Wenhao Hou; Zhuowei Zhang; Zhennan Shi; Jingye Yang (Water Research, 2026)

Acute exercise activates hepatic Nrf2 signaling by ROS, AMPK and epinephrine to protect against acute liver injuries - Simin Yang; Ranting Zhao; Li Lei; Xiangbo An; Jiangli Xu; Han Xu; Jiahui Wang; Han Xiao; Youyi Zhang; Xiaoda Yang; Siwang Yu (Toxicology and Applied Pharmacology, 2026)

Distributed three-dimensional target enclosing control for AUVs under ocean currents - Linlin Shi; Haoming Wu; Biao Wei; Simin Lv; Yang Xu; Ronghao Zheng; Yu Chen (Ocean Engineering, 2026)

Study on the extraction, purification and anti-ageing activity of polydatin in Reynoutria japonica Houtt - Simin Yang; Xiaotong Qin; Mingwei Jia; Xiaoming Peng; Xiaoqiang Yan; Jie Guan; Ruijun Ju (Natural Product Research, 2026)

Ammonia–hypoxia co-stress induces intestinal injury, antioxidant dysregulation, and microbial dysbiosis in Macrobrachium rosenbergii - Nusrat Liaqat; Xuenan Li; Huici Yang; Nauman Khan; Nader N. Hassona; Simin You; Xilin Dai (Aquaculture, 2026)

Lactobacillus plantarum ameliorates intrahepatic cholestasis by modulating the gut microbiota and tryptophan metabolism - Shijing Dong; Liping Guo; Chenyang Xuan; Chenhui Zhu; Zongze Han; Nian Chen; Xinyu Wang; Meng Shen; Xiaoxuan Wei; Hui Yang; Xue Zhang; Man Liu; et al. (Food Research International, 2026)

Mobile genetic elements drive the assembly of high-risk resistance and virulence configurations at the riverine water–sediment interface - Jingru Yang; Xin Meng; Hongzheng Zhang; Wanchen Sun; Linzhen Yang; Simin Li (Environmental Research, 2026)

Simultaneous nitrogen and fluoride removal from photovoltaic wastewater via a microalgal-bacterial consortia: Performance and fluorapatite biomineralization - Simin Liao; Ling Lai; Zhensheng Xiong; Suhua Chen; Gengxin Zhou; Chenghang Tu; Wei Ren; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2026)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury after SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2026)

Temperature and ethanol synergistically enhance microplastic release from disposable cups: mechanistic insights and health risk assessment of typical plastics - Simin Li; Linzhen Yang; Xin Meng; Wanchen Sun; Hongzheng Zhang; Jingru Yang (ENGINEERING Environment, 2026)

Phosphorus source identification in a human-impacted small watershed using phosphate oxygen isotopes - Jiaxuan Zhang; Xin Jin; Qingxuan Wu; Hao Wang; Jing Yang; Simin Li; Wenqiang Zhang (Aquatic Sciences, 2026)

Role of heterogeneity of counter-diffusional biofilm on microaeration-assisted for nitrophenol degradation: Metabolic pathways and microbial mechanisms - Zhuowei Zhang; Simin Li; Jing Guo; Yin Yu; Wenhao Hou; Jingye Yang (Journal of Water Process Engineering, 2026)

Enhancing taste without salt or sugar: Cross-modal flavor modulation via olfactory cues - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

Lactiplantibacillus plantarum GUANKE Alleviates Intestinal Barrier Damage Caused by Influenza Infection in Mice - Kun Yue; Simin Lu; Tao Yang; Jielan Mi; Siqin He; Hanyu Ma; Yujia He; Zhihan Yang; Yuanming Huang; Liqiong Song; Zhihong Ren; Lili Ren; et al. (Probiotics and Antimicrobial Proteins, 2026)

Melatonin alleviates cholestatic liver injury through modulating gut microbiota and activating the NRF2/HO-1 antioxidant pathway - Shijing Dong; Jiangpeng Liu; Chenyang Xuan; Simin Zhou; Zongze Han; Chenhui Zhu; Nian Chen; Ruiyun Liu; Weirong Wang; Hongyu Chu; Xue Zhang; Hui Yang; et al. (Tissue and Cell, 2026)

Distinct assembly mechanisms, functional traits and pathogenic risks of the plastisphere microbiome in a freshwater lake: Evidence from Baiyangdian Wetland - Simin Li; Wanchen Sun; Xuguang Tian; Xin Meng; Linzhen Yang; Hongzheng Zhang; Jingru Yang (Journal of Environmental Chemical Engineering, 2026)

Targeting critical zones: A review of heterogeneity identification methods and driving mechanisms of watershed phosphorus transport - Qingxuan Wu; Rang Wang; Jing Yang; Hao Wang; Simin Li; Xin Jin (Journal of Contaminant Hydrology, 2026)

Acceleration of exciton radiative recombination in Zn-alloyed 0D/3D heterostructure perovskite scintillators for efficient X-ray imaging - Huiwang Lian; Rongyi Kuang; Meng Gao; Simin Gu; Siran Tao; Yang Li; Jing Wang; Jianxin Shi (Chemical Engineering Journal, 2026)

Phthalate exposure and hepatocellular carcinoma: Unraveling mechanisms through network toxicology - Simin Zhan; Chun Li; Kaiyi Zeng; Yanhao Ran; Chenyu Liu; Yunshuo Zhang; Zekai Zeng; Chuntian Wang; Ziqing Yang (Toxicology, 2025)

Dynamic development of global contiguous flash droughts: from an event-based spatiotemporal perspective - Dingkui Wang; Xuezhi Tan; Xinxin Wu; Zeqin Huang; Simin Deng; Yaxin Liu; Jianyu Fu; Xuejin Tan; Xitian Cai; Bingjun Liu; Haiyun Shi; Long Yang; et al. (Journal of Hydrology, 2025)

Microplastic pollution steers stochastic assembly and biases predicted C–N functional potentials in lake sediments - Simin Li; Jingru Yang; Xin Meng; Hongzheng Zhang; Wanchen Sun; Linzhen Yang (Journal of Environmental Chemical Engineering, 2025)

Plant sterol ester-modified naringenin liposomes: A novel strategy for effectively penetrating the mucus barrier - Liuqing Yang; Jingjian Liu; Shuqi Liang; Baihui Guo; Gaodan Liu; Tarun Belwal; Simin Feng (Food Research International, 2025)

L-theanine protects against acute alcohol-induced brain injury via cGMP/PKG signaling activation - Jiahao Yang; Xuhui Dang; Simin Tan; Jiayou Gu; Kehong Liu; Zhihua Gong; Wenjun Xiao (Food Bioscience, 2025)

Incorporating quercetin nanocrystals in chitosan-polyvinyl alcohol composite film with cinnamon essential oil loaded Pickering emulsions for enhanced controlled release properties - Simin Fan; Dequan Zhang; Qingfeng Yang; Chaoqiao Zhu; Aurore Richel; Marie-Laure Fauconnier; Cheng Li; Ming Tian; Xin Li; Chengli Hou (Food Packaging and Shelf Life, 2025)

Numerical simulation of hyporheic exchange and analysis of driving mechanisms in the tidal Jingzi River, China - Jingwen Xing; Yi Cai; Nianqing Zhou; Yang Xian; Simin Jiang; Yupeng Zhou; Anjun Huang; Dongze Yi (Hydrogeology Journal, 2025)

Oxidative stress and ferroptosis in diabetic cardiomyopathy: mechanistic interplay and therapeutic implications - Shan Li; Yuhe Shu; Shuyu Yang; Simin Zhang; Haoling Chen; Dan Wu; Bo Li; Li Dong (Apoptosis, 2025)

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Thiol collectors removal from simulated tailings wastewater by batch electrocoagulation using copper electrodes - Gaogui Jing; Shenggui Zhao; Xinxing Liang; Huai Wang; Simin Yang; Wei Sun; Zhiyong Gao (Minerals Engineering, 2025)

Soil Water Accounting Network (SWAN): a novel neural network for modeling conceptual hydrological processes - Zheng Fang; Simin Qu; Ziheng Li; Qiongfang Li; Peng Shi; Yiqun Sun; Xiaoqiang Yang; Han Tang; Junfang Zhang; Zhengxian Zhu; Hongshi Wu; Weimin Bao (Journal of Hydrology, 2025)

Reinforcement of chitosan/ polyvinyl alcohol film by quercetin self-assembled nanocrystals for fresh meat preservation - Simin Fan; Wenxin Wang; Qingfeng Yang; Chaoqiao Zhu; Ming Tian; Aurore Richel; Marie-Laure Fauconnier; Chengli Hou; Dequan Zhang (Food Chemistry, 2025)

Naringenin-loaded Flammulina velutipes chitin-glucan complexes gel system: structural modulation and dual lipid-lowering mechanisms - Simin Feng; Shuqi Liang; Jianyu Yang; Jiahao Yu; Yang Lin; Yizhen Xie; Peilong Sun; Ping Shao (Food Chemistry, 2025)

Comparative study of thermodynamic and material planetary boundary layer height in Beijing during the heatwaves - Lindong Dai; Yongnan Zhang; Yongjing Ma; Simin Yang; Zengshou Liu; Pengkun Ma; Yubing Pan; Zhiheng Liao; Shao Xiao; Yunjie Xia; Li Lu; Danjie Jia; et al. (Advances in Space Research, 2025)

Novel receptor-binding protein from phage PJNS004 for sensitive detection of Salmonella - Yibao Chen; Simin Yang; Qing Zhang; Ming Hu; Qianghua Lv; Xiaonan Zhao; Lulu Li; Yanbo Luo; Xiaohui Xu; Yujun Zhao; Yuqing Liu (Food Chemistry, 2025)

Influence of biopolymer-based topsoil treatments on surface-subsurface hydrological processes: Implications for protection and restoration of sandy slopes - Jin Liu; Runqi Zhang; Miao Jing; Simin Yang; Zezhuo Song; Wenyue Che (CATENA, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Anion competitive coordination for solvation structure regulation in high-voltage sodium-ion batteries - Bowen Zhu; Jingkai Gao; Simin Li; Wei Zhou; Zhendong Yang; Rui Jin; Yi Zhang; Zixuan Ding; Yanqing Lai; Jie Li; Zhian Zhang (Chemical Engineering Journal, 2025)

A synergistic water-saving strategy combining stage-specific irrigation and application of exogenous thiamine enhances drought resistance of Xinjiang cotton - Fuxiang Zhao; Linjie Xia; Simin Sun; Hang Li; Yuxuan Rong; Yuxin Wang; Xuwen Wang; Xianhui Kong; Longfu Zhu; Xianlong Zhang; Yu Yu; Xiyan Yang (Plant and Soil, 2025)

Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2025)

All-in-one detecting dairy iodine based on single drop microextraction coupled with ratiometric fluorescence filter effect - Ruiqi Gao; Simin Ye; Xiaofang Yang; Ying Zhang; Yuanyuan Liu; Jinyi Zhang; Chengbin Zheng (Food Chemistry, 2025)

Ratio-fluorescence detection of propyl gallate based on MnOOH nanoflakes and β-cyclodextrin modified quantum dots - Bo Peng; Fengxiang Du; Simin Dou; Yuying Yang; Min Zhou; Shengguo Zhao; Yanjun Fang (Food Chemistry, 2025)

Enhancing water security in lake basins through geographic intelligence technology - Yong Ge; Li Zhang; Yi Han; Die Zhang; Wenjing Yang; Lian Feng; Jinwei Dong; Shuping Wang; Simin Peng; Chaoyang Fang (Science Bulletin, 2025)

Characterization and removal of surface oligomers on polyester yarns dyed in decamethylcyclopentasiloxane waterless dyeing system - Simin Sun; Liujun Pei; Qinggai Zhang; Hao Li; Mingxuan Yang; Gang Sun; Jiping Wang (Journal of Environmental Chemical Engineering, 2025)

Sustainable nanofiber films based on polylactic acid/modified cellulose nanocrystals containing various types of polyphenols, exhibiting antioxidant activity and high stability - Chaoqiao Zhu; Qingfeng Yang; Ming Tian; Wei Yang; Chengjun Min; Simin Fan; Debao Wang; Xin Li; Dequan Zhang; Chengli Hou (Food Chemistry, 2025)

Mendelian randomization and multi-omics analysis identify C4A as a critical protective biomolecule in head and neck squamous cell carcinoma - Ziqing Yang; Xinhui Qiu; Anquan Ma; Chenyang Wu; Xiaoyang Zong; Yifei Nie; Simin Zhan; Haoran Yang; Chengyuan Zhang; Huilu Song; Xu Wang; Zhihong Zhang; et al. (Chemical Engineering Journal, 2025)

Cerebral [18F]AIF-FAPI-42-Based PET Imaging of Fibroblast Activation Protein for Non-invasive Quantification of Fibrosis After Ischemic Stroke - Peipei Tang; Yang Liu; Simin Peng; Zhikai Cai; Ganghua Tang; Zhou Zhou; Kongzhen Hu; Yuhua Zhong (Translational Stroke Research, 2025)

Selective recovery of rare earth elements from mine wastewater using the magnetic zeolite prepared by rare earth tailings - Jianhui Zhang; Jianchen Cheng; Guizhou Xu; Xuechao Hou; Zhifei Yu; Wei Liu; Yalan Zhang; Jianxin Chen; Jiahao Yang; Mengting Wu; Wanqing Yang; Simin Li; et al. (Chemical Engineering Journal, 2025)

Carbon dioxide and methane fluxes in different waterbodies in Inexpressible Island, Ross Sea, East Antarctica - Zhiheng Du; Lei Wang; Simin Xie; Jiao Yang; Fangping Yan; Chuanjin Li; Minghu Ding; Yuzhu Zhang; Xi Ding; Cunde Xiao (Marine Pollution Bulletin, 2025)

The interaction of atmospheric boundary layer and PM pollution in Mongolian Plateau: Implication for the threshold control strategy - Simin Yang; Yongjing Ma; Wenyu Zhang; Zhong Lin; Zhenguo Lu; Xingjun Zhou; Yuanzhe Ren; Xinbing Ren; Kecheng Peng; Yulong Tan; Yiming Wei; Masroor Ahmad; et al. (Atmospheric Research, 2025)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)

Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)
Subarachnoid hemorrhage (SAH) is a type of stroke with a high disability and mortality rate. Apoptosis caused by massive damage to mitochondria in neuron cells and inflammatory responses caused by high extracellular ATP lead to poor outcomes. USP30 is a deubiquitinating enzyme that inhibits mitophagy, resulting in a failure to remove damaged mitochondria in a timely manner after SAH; nevertheless, the pathway through which USP30 inhibits mitophagy is unknown. This study evaluated the neuroprotective role and possible molecular basis by which inhibiting USP30 to attenuate SAH-induced EBI by promoting neuronal mitophagy. We used an in vitro model of hemoglobin exposure and an in vivo model of intravascular perforation. Increased expression of USP30 was found after SAH in vivo and in vitro, and USP30 inhibition expression in SAH mice treated with MF094 resulted in significant improvement of neurological injury and inflammatory response and mediated good outcomes, suggesting a neuroprotective effect of USP30 inhibition. In cultured neurons, inhibition of USP30 promoted ubiquitination modification of mitochondrial fusion protein 2 (MFN2) by E3 ubiquitin ligase (Parkin), separating damaged mitochondria from the healthy mitochondrial network and prompting mitophagy, causing early clearance of damaged intracellular mitochondria, and reducing the onset of apoptosis. The high extracellular ATP environment was meliorated, reversing the conversion of microglia to a pro-inflammatory phenotype and reducing inflammatory injury. USP30 inhibition had no autophagy-promoting effect on structurally and functionally sound mitochondria and did not inhibit normal intracellular ATP production. The findings suggest that USP30 inhibition has a neuroprotective effect after SAH by promoting early mitophagy after SAH to clear damaged mitochondria.

Understanding the Antidepressant Mechanisms of Acupuncture: Targeting Hippocampal Neuroinflammation, Oxidative Stress, Neuroplasticity, and Apoptosis in CUMS Rats - Jianguo Li; Xinhong Wu; Simin Yan; Junliang Shen; Tao Tong; Muhammad Shahzad Aslam; Jingyu Zeng; Yiping Chen; Wenjie Chen; Meng Li; Zhuoran You; Kaiyue Gong; et al. (Molecular Neurobiology, 2025)

Pollution profiles, pathogenicity, and toxicity of bioaerosols in the atmospheric environment of urban general hospital in China - Simin Huang; Yuxuan Wei; Weibang Yang; Yufei Zhao; Qiwen Wang; Ranjit Das; Chunyou Zhu; Xiaofeng Jiang; Zhishu Liang (Environmental Pollution, 2025)

Adaptive Surrogate Model Assisted Swarm Intelligence for Parameter Inversion of complex hydrological models - Guhan Li; Peng Shi; Simin Qu; Lingzhong Kong; Xiaohua Xiang; Qian Yang; Yu Qiao; Shiyu Lu (Environmental Modelling & Software, 2025)

One-step construction of FeP/carbon aerogel composites and their efficient tetracycline removal mechanisms: Adsorption, in situ oxygen activation and electron transfer - Guilong Wang; Rongyuan Jiang; Juntao Chen; Simin Li; Guanfeng Lin; Beili Lu; Biao Huang; Jianwei Zhao; Lei Yang (Journal of Water Process Engineering, 2025)

A benchmark of industrial polymerization process for thermal runaway process monitoring - Simin Li; Shuang-hua Yang; Yi Cao; Xiaoping Jiang; Chenchen Zhou (Process Safety and Environmental Protection, 2025)

Removal of heavy metals from water by adsorption on metal organic frameworks: Research progress and mechanistic analysis in the last decade - Fang Yuan; Dingfan Yan; Shuaibo Song; Jinbo Zhang; Yangyang Yang; Zheng Chen; Jiahao Lu; Simin Wang; Yongjun Sun (Chemical Engineering Journal, 2025)

Versatile benzthienocarbazole isomer derivatives as efficient TADF emitters and hosts for blue multi-resonance TADF emitters - Deli Li; Jiaji Yang; Simin Jiang; Haoxiang Yuan; Denghui Liu; Zhihai Yang; Guo-Xi Yang; Mengke Li; Xuchuan Jiang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2025)

Ball milling of pyrolytic residue from oil sands with MnO2 and reuse as PMS activator: Measurement of ROS exposure and mechanism insights - Simin Song; Yifan Yang; Xinxing Pan; Xiaojuan Chai; Mingxin Wang (Process Safety and Environmental Protection, 2024)

Formation of flake-like DAAF crystals with tunable size realized on a microfluidic platform for binder-free initiator explosives - Bo Yang; Shengshu Xi; Simin He; Jin Chen; Wei Cao; Rui Li; Rupeng Bu; Xiaona Huang; Jincan Zhu; Qi Wu; Weimiao Wang; Xiaodong Li; et al. (Chemical Engineering Journal, 2024)

Associations of occupational exposure to micro-LiNiCoMnO2 particles with systemic inflammation and cardiac dysfunction in cathode material production for lithium batteries - Yaotang Deng; Guoliang Li; Lijie Xie; Xiaoliang Li; Youyi Wu; Jiewei Zheng; Simin Xian; Jiazhen Zhou; Jiabin Chen; Yuewei Liu; Qiaoyuan Yang; Qing Wang; et al. (Environmental Pollution, 2024)

Local defect structure design enhanced energy storage performance in lead-free antiferroelectric ceramics - Peixuan Li; Simin Wang; Jin Qian; Guanglong Ge; Luomeng Tang; Jinfeng Lin; Weiwei Yang; Jimin Lin; Weikang Lin; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2024)

Inorganic salts released from polypyrrole nanocapsules on compact TiO2 layer for highly efficient inorganic CsPbI3-type perovskite solar cells - Dan Li; Xin Li; Kang Wang; Simin Ma; Xin Shao; Tingting Yang; Yunhui Han; Zhengguo Zhang; Shengzhong Liu; Shengwei Guo (Chemical Engineering Journal, 2024)

Self-assembled Chitosan/Polyvinyl alcohol hydrogel film incorporated with TiO2 with excellent stability, mechanical and antibacterial properties for the preservation of chilled pork - Debao Wang; Juan Chen; Xiangyuan Wen; Simin Fan; Chaoqiao Zhu; Xin Li; Fei Fang; Wei Yang; Wenchun Fan; Dequan Zhang; Chengli Hou (Food Packaging and Shelf Life, 2024)

Genomic insights into adaptation to bipedal saltation and desert-like habitats of jerboas - Simin Chai; Yujie Chong; Daiqing Yin; Qiang Qiu; Shixia Xu; Guang Yang (Science China Life Sciences, 2024)

Pediococcus pentosaceus MIANGUAN Enhances the Immune Response to Vaccination in Mice - Yulu Chen; Zhijie Cao; Simin Lu; Zhihuan Wang; Caiyun Ma; Gui Zhang; Mengshan Chen; Jing Yang; Zhihong Ren; Jianguo Xu (Probiotics and Antimicrobial Proteins, 2024)

Zein and tannic acid hybrid particles improving physical stability, controlled release properties, and antimicrobial activity of cinnamon essential oil loaded Pickering emulsions - Simin Fan; Qingfeng Yang; Debao Wang; Chaoqiao Zhu; Xiangyuan Wen; Xin Li; Aurore Richel; Marie-Laure Fauconnier; Wei Yang; Chengli Hou; Dequan Zhang (Food Chemistry, 2024)

AI model to improve the mountain boundary layer height of ERA5 - Jinyuan Xin; Kecheng Peng; Xiaoqian Zhu; Xiaole Pan; Qiyuan Wang; Junji Cao; Zifa Wang; Xiaoqun Cao; Xinbing Ren; Simin Yang; Yiming Wei; Dandan Zhao; et al. (Atmospheric Research, 2024)

How does the biochar-supported sulfidized nanoscale zero-valent iron affect the soil environment and microorganisms while remediating cadmium contaminated paddy soil? - Wenjing Xue; Siqi Wen; Xinyu Chen; Yu Wang; Simin Qian; Yiyun Wu; Rongrong Ge; Yang Gao; Yiqun Xu (Environmental Geochemistry and Health, 2024)

Investigating the potential of EMA-embedded feature selection method for ESVR and LSTM to enhance the robustness of monthly streamflow forecasting from local meteorological information - Lei Xu; Peng Shi; Hongshi Wu; Simin Qu; Qiongfang Li; Yiqun Sun; Xiaoqiang Yang; Peng Jiang; Chao Qiu (Journal of Hydrology, 2024)

H2S is involved in drought-mediated stomatal closure through PLDα1 in Arabidopsis - Simin Wang; Cuixia Zhang; Rongshan Chen; Kailin Cheng; Liai Ma; Wei Wang; Ning Yang (Planta, 2024)

Arsenic field test kits based on solid-phase fluorescence filter effect induced by silver nanoparticle formation - Wenhui Yang; Liqing Ye; Yuke Wu; Xi Wang; Simin Ye; Yurong Deng; Ke Huang; Hong Luo; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2024)

An innovative in situ solvent generation enhanced SAGD technique: Mechanism analysis based on numerical simulation - Simin Yang; Siyuan Huang; Qi Jiang; Guanchen Jiang; Xiang Zhou; Chunsheng Yu (Fuel, 2024)

Tailoring sweetness sensitivity cued by affective pictures - Ying Wen; Huajing Yang; Zhile Kang; Liuqing Wei; Simin Zhao; Pei Liang (Food Quality and Preference, 2024)

Enhancing acid stability of citral through internal structure modulation in nanostructured lipid carriers with solid lipids and phospholipids - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Research International, 2024)

Advancing real-time error correction of flood forecasting based on the hydrologic similarity theory and machine learning techniques - Peng Shi; Hongshi Wu; Simin Qu; Xiaoqiang Yang; Ziheng Lin; Song Ding; Wei Si (Environmental Research, 2024)

A nested case-control study of serum zinc and incident diabetes among Chinese adults: Effect modifications and mediation analysis - Jingli Yang; Zhiyuan Cheng; Desheng Zhang; Tongzhang Zheng; Chun Yin; Simin Liu; Lizhen Zhang; Zhongge Wang; Yufeng Wang; Ruirui Chen; Qian Dou; Yana Bai (Science of The Total Environment, 2024)

Obscuring effect of income inequality and moderating role of financial literacy in the relationship between digital finance and China's household carbon emissions - Simin Huang; Lin Yang; Chen Yang; Donghan Wang; Yiming Li (Journal of Environmental Management, 2024)

A hydrologic similarity-based parameters dynamic matching framework: Application to enhance the real-time flood forecasting - Hongshi Wu; Peng Shi; Simin Qu; Xiaoqiang Yang; Hongxue Zhang; Le Wang; Song Ding; Zichun Li; Meixia Lu; Chao Qiu (Science of The Total Environment, 2024)

Golgi-triggered radiation sensitizer retention enhances the efferocytosis and immunotherapy in breast cancer with skeleton metastases - Yi-chuan Pang; Xiaotong Qiu; Simin Liu; Yanlei Huo; Xiaoli Yang; Chao Ma; Min qi; Xiaojun Chen; Zhi-hang Zhou; Zhongwei Lv (Chemical Engineering Journal, 2024)

Comparative miRNA-seq analysis revealed molecular mechanisms of red color formation in the early developmental stages of Plectropomus leopardus - Xi Liu; Mouyan Jiang; Simin Wen; Kaixiang Zhang; Yucong Hong; Kaihui Sun; Xianwu Deng; Yang Huang; Gang Shi; Changxu Tian; Huapu Chen; Guangli Li; et al. (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play important roles in several biological processes, including the regulation of body color. Leopard coral grouper ( Plectropomus leopardus ) is a valuable marine aquaculture fish; however, at present, there are no published reports on its early body color development. The skin color of P. leopardus undergoes a transition from transparent to red from 26 days post-hatching (dph) to 30 dph. In this study, we performed miRNA sequencing on 26 dph (Transparent, PT) and 30 dph (Red, PR) skin samples of P. leopardus to explore the molecular mechanism underlying red color formation. A total of 44.31 M and 37.55 M clean tags were obtained from PT and PR group, respectively. Among these tags, 981 miRNAs were identified, including 493 known and 488 novel miRNAs. A total of 106 differentially expressed miRNAs (DEMs) were identified in PT vs. PR, with 43 up-regulated and 63 down-regulated miRNAs in the PR group, compared to the PT group (|fold change| > 2 and p-value < 0.05). A miRNA-mRNA network based on 18 candidate miRNAs and 53 target genes related to pigmentation, and KEGG enrichment analysis of the target genes of all DEMs, revealed that miRNAs involved in the formation of red skin color were mainly related to: 1) the inhibition of melanin synthesis (miR-141-z, miR-206-z, miR-206-y, miR-27-z, miR-137-y, miR-204-x, miR-204-y, miR-211-x, miR-211-z); 2) chromatophore development (miR-206-z, miR-206-y, miR-499-y, miR-1-z, miR-2188-x, miR-423-x); and 3) carotenoid metabolism (miR-204-x, miR-204-y, miR-499-y). This study demonstrates the potential role of miRNAs in red color formation and lays the foundation for the molecular mechanism of body color polymorphism in P. leopardus .

Encapsulation and release of citral using nanostructured lipid carriers: A study on the impact of different preparation methods - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Bioscience, 2023)

Urban rainstorm and waterlogging scenario simulation based on SWMM under changing environment - Simin Wang; Rengui Jiang; Mingxiang Yang; Jiancang Xie; Yinping Wang; Wen Li (Environmental Science and Pollution Research, 2023)

Comparison of transit time models for exploring seasonal variation of preferential flow in a Moso bamboo watershed - Jianfeng Gou; Simin Qu; Peng Shi; Huade Guan; Hai Yang; Zhicai Zhang; Jintao Liu; Zhiguo Su (Journal of Hydrology, 2023)

Tropical ocean temperatures and changes in terrigenous flux during the Paleocene-Eocene Thermal Maximum in southern Tibet - Simin Jin; Guobiao Li; Juan Li; Xiumian Hu; Huan Yang; Chunju Huang; Zhantu Baoke; Thomas J. Algeo; David B. Kemp (Global and Planetary Change, 2023)

Study on components selection and performance of bio-oil based asphalt rejuvenator based on softening and asphaltene deagglomeration effect - Qunshan Ye; Zhiyu Yang; Songtao Lv; Jiao Jin; Simin Zhang (Journal of Cleaner Production, 2023)

Residual behavior and dietary risk assessment of albendazole as fungicide in citrus orchards - Lihua Yang; Simin Yao; Anugerah Fajar; Austin Merchant; Jizhe Shi; Haifeng Luo; Zhaoxia Qing; Yaocheng Deng; Xiangwei Tang; Daoxin Gong; Xuguo Zhou (Food Chemistry, 2023)

Applicability assessment of five evapotranspiration models based on lysimeter data from a bioretention system - Wenlong Zhang; Moyuan Yang; Shouhong Zhang; Lei Yu; Fei Zhao; Duwei Chen; Simin Yang; Hualin Li; Sunxun Zhang; Ruixian Li; Jianjun Zhang (Ecological Engineering, 2023)

Detection and quantitative analysis of tumor-associated tertiary lymphoid structures - Man Yang; Yurou Che; Kezhen Li; Zengyi Fang; Simin Li; Mei Wang; Yiyao Zhang; Zhu Xu; Liping Luo; Chuan Wu; Xin Lai; Weidong Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Highly sensitive and ratiometric detection of nitrite in food based on upconversion-carbon dots nanosensor - Yaqing Yang; Simin Wei; Jialin Wang; Junjie Li; Jinlu Tang; Albert Aryee Aaron; Qiyong Cai; Ningning Wang; Zhaohui Li (Analytica Chimica Acta, 2023)

Design, synthesis and mechanism study of novel natural-derived isoquinoline derivatives as antifungal agents - Wei Chen; Rui Zhang; Yang Chen; Pingbing Yu; Yuxin Lan; Haojian Xu; Simin Lei (Molecular Diversity, 2023)

A social-ecological coupling model for evaluating the human-water relationship in basins within the Budyko framework - Bohua Wu; Quan Quan; Simin Yang; Yuxiang Dong (Journal of Hydrology, 2023)

Effect of Distinct Evaluation Objectives on Different Precipitation Downscaling Methods and the Corresponding Potential Impacts on Catchment Runoff Modelling - Xumin Zhang; Simin Qu; Jijie Shen; Yingbing Chen; Xiaoqiang Yang; Peng Jiang; Peng Shi (Water Resources Management, 2023)

Seasonal variation of transit time distribution and associated hydrological processes in a Moso bamboo watershed under the East Asian monsoon climate - Jianfeng Gou; Simin Qu; Huade Guan; Peng Shi; Zhicai Zhang; Hai Yang; Jintao Liu; Zhiguo Su; Xiaole Han (Journal of Hydrology, 2023)

Spiral donor-based host materials for highly efficient blue thermally activated delayed fluorescence OLEDs - Deli Li; Mengke Li; Wei Li; Wenqi Li; Zijian Chen; Xiaomei Peng; Denghui Liu; Guo-Xi Yang; Simin Jiang; Yiyang Gan; Zhihai Yang; Kunkun Liu; et al. (Chemical Engineering Journal, 2023)

Planar D-σ-A type thermally activated delayed fluorescence material with Intra- and intermolecular charge transfer characteristics - Simin Jiang; Jianyin Lin; Deli Li; Mengke Li; Yanmei He; Wentao Xie; Jiting Chen; Yiyang Gan; Guo-Xi Yang; Zhihai Yang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2023)

Assessing the total factor productivity growth decomposition: the transformation of economic growth momentum and policy choice in China - Feng Luo; Feng Chen; Dandan Yang; Simin Yang (Environmental Science and Pollution Research, 2022)

MicroRNA-196a-5p overexpression in Wharton’s jelly umbilical cord stem cells promotes their osteogenic differentiation and new bone formation in bone defects in the rat calvarium - Yantong Wang; Simin Zhang; Haoqing Yang; Yangyang Cao; Dianqin Yu; Yingchu Zhao; Yu Cao (Cell and Tissue Research, 2022)

A review on chemical and physical modifications of phytosterols and their influence on bioavailability and safety - Simin Feng; Liling Wang; Ping Shao; Peilong Sun; Chung S. Yang (Critical Reviews in Food Science and Nutrition, 2022)

Effects of Shear Stress and Salinity Stratification on Floc Size Distribution During the Dry Season in the Modaomen Estuary of the Pearl River - Jie Huang; Simin Wang; Xinran Li; Rongyao Xie; Jianxiong Sun; Benwei Shi; Feng Liu; Huayang Cai; Qingshu Yang; Zhaoyong Zheng (Frontiers in Marine Science, 2022)
The floc size distribution of fine cohesive sediments in estuaries varies spatiotemporally within assorted physical, chemical, and biological factors. However, the distribution of different floc fractions that are affected by shear stress and salinity stratification has not yet been thoroughly investigated. This study intends to clarify the floc size distribution within the influences of turbulent shear rate and salinity stratification, and the implications for the flocculation process during the dry season in the Modaomen Estuary of the Pearl River. The decomposition of multimodal floc size distributions (FSDs) indicates that the floc fractions were composed of macroflocs (Macro), microflocs (Micro), Flocculi, and primary particles (Pp). Macro generally existed among the upper and middle layers, but smaller flocs, i.e., Micro, Flocculi, and Pp, were mostly concentrated in the bottom layer. The results agreed that the flocculation and deflocculation processes were dominant in the upper and bottom layers, respectively. In response to strong turbulent shear rates, FSDs in the bottom layer skewed toward small sizes and had a dual-peak tendency with frequent floc exchanges between Pp and Micro, then being Pp-dominant but converting to Micro when turbulent shear rates decreased. With impeded vertical mixing by salinity stratification, the FSDs in the upper or middle layers skewed toward a larger particle size with single peaks and lack of exchange among different floc fractions, leading to Macro dominance with a larger volume concentration and median size. In addition, turbulence mixing dramatically interfered with the good mixing of floc fractions amidst the vertical water column, with a low-salinity condition greatly affecting the formation of Macro in the bottom layer within proper turbulent shear rates. This study explores the effects of shear stress and salinity stratification on the flocculation process in the Modaomen Estuary, which contributes to a better understanding of sediment movement in a complex estuarine environment.

SbbHLH85, a bHLH member, modulates resilience to salt stress by regulating root hair growth in sorghum - Yushuang Song; Simin Li; Yi Sui; Hongxiang Zheng; Guoliang Han; Xi Sun; Wenjing Yang; Hailian Wang; Kunyang Zhuang; Fanying Kong; Qingwei Meng; Na Sui (Theoretical and Applied Genetics, 2022)

Streptomyces luteolifulvus sp. nov., a novel actinomycete isolated from soil in Nanjing, China - Shanshan Zhao; Ming Cheng; Congyu Lin; He Liu; Zhengran Wang; Kai Zhang; Simin Song; Qian Yang (Antonie van Leeuwenhoek, 2021)

Enhanced Negative Regulation of the DHH Signaling Pathway as a Potential Mechanism of Ascrotal Testes in Laurasiatherians - Simin Chai; Ran Tian; Ying Yang; Guang Yang; Shixia Xu; Wenhua Ren (Evolutionary Biology, 2021)

Circ_0114876 promoted IL-1β-induced chondrocyte injury by targeting miR-671/TRAF2 axis - Qiushi Wang; Simin Luo; Jie Yang; Jieruo Li; Songwei Huan; Guorong She; Zhengang Zha (Biotechnology Letters, 2021)

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

Taxonomic revision of the Long-tailed Rosefinch Carpodacus sibiricus complex - Simin Liu; Chentao Wei; Paul J. Leader; Geoff J. Carey; Chenxi Jia; Yinan Fu; Per Alström; Yang Liu (Journal of Ornithology, 2020)

Propofol ameliorated diabetic peripheral neuropathic pain via modulating miR-150/EPHB2 axis - Dongyi Fan; Simin Yang; Jingyu Yao; Yuxiang Han; Lukun Yang (Molecular & Cellular Toxicology, 2020)

Aldehyde dehydrogenase-positive melanoma stem cells in tumorigenesis, drug resistance and anti-neoplastic immunotherapy - Simin Zhang; Zhen Yang; Fazhi Qi (Molecular Biology Reports, 2020)

Correction to: Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Spatial optimization mode of China’s rural settlements based on quality-of-life theory - Xu Juan; Ma Hongtu; Luo Jing; Huo Xiaoping; Yao Xingbo; Yang Simin (Environmental Science and Pollution Research, 2019)

The protective microRNA-199a-5p-mediated unfolded protein response in hypoxic cardiomyocytes is regulated by STAT3 pathway - Yang Zhou; Bo Pang; Yingbin Xiao; Simin Zhou; Bin He; Fan Zhang; Wei Liu; Huali Peng; Peng Li (Journal of Physiology and Biochemistry, 2019)

Imidazole-Bearing Polymeric Micelles for Enhanced Cellular Uptake, Rapid Endosomal Escape, and On-demand Cargo Release - Di Lu; Yang An; Simin Feng; Xiaodan Li; Aiping Fan; Zheng Wang; Yanjun Zhao (AAPS PharmSciTech, 2018)

Characteristics Analysis of Summer Maize Yield Loss Caused by Drought Stress in the Northern Huaihe Plain, China - Simin Geng; Denghua Yan; Zhiyong Yang; Zhongbo Zhang; Meijian Yang; Guangyuan Kan (Irrigation and Drainage, 2018)
Summer maize is a major crop in the Northern Huaihe Plain. To simulate maize yield losses caused by drought stress in 13 cities, the DSSAT‐CERES‐Maize model was selected as a tool, which was calibrated and validated based on drought stress experimental observations conducted in 2013 in Bengbu, China. Results indicate the numbers of years of low, low‐mid, mid, mid‐high and high loss percentage as 25–37, 3–9, 1–6, 0–5 and 1–13, respectively. There was a higher risk of high loss percentage in the south, with higher risk of low‐mid loss percentage in the north‐east and higher risk of mid‐high loss percentage in the west. Compared with the proportion of high loss percentage during 1961–1980, in the high loss percentage years, it decreased by 5–30% in the south and increased by 1–15% in the south‐west during 1981–2015. However, in mid‐high loss percentage years, the proportion increased by 5–25% in the north, with less change in other areas. In low‐mid loss percentage years, the proportion increased by 5–20% in the south‐east and decreased by 5–34.4% in the north. The yield loss decreased on average 766 000 t and 15% after rational allocation of water resources, which improves drought resistance in the Northern Huaihe Plain. Copyright © 2017 John Wiley & Sons, Ltd.

Divergent Selection of Pattern Recognition Receptors in Mammals with Different Ecological Characteristics - Ran Tian; Meixiu Chen; Simin Chai; Xinghua Rong; Bingyao Chen; Wenhua Ren; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2018)

Dibenzoylmethane Protects Against CCl4-Induced Acute Liver Injury by Activating Nrf2 via JNK, AMPK, and Calcium Signaling - Mingnan Cao; Huixia Wang; Limei Guo; Simin Yang; Chun Liu; Tin Oo Khor; Siwang Yu; Ah-Ng Kong (The AAPS Journal, 2017)